Many a little makes a mickle: Why do consumers negatively react to sequential price disclosure?. Issue 1 (23rd October 2020) - Totzek, Dirk; Jurgensen, Gabriel
Abstract: Drip pricing (DP) is distinct from partitioned pricing as it sequentially discloses surcharges to consumers. Critics see DP as a deceptive pricing tactic because it obscures the final price of an offer. We examine the effects of the timing of the final price disclosure and the number of sequentially presented surcharges on consumers' attention to the final price and, ultimately, perceived price fairness. In an eye‐tracking study with 225 participants, we find that the sequential (vs. up‐front) disclosure of the final price lowers perceived price fairness by increasing consumers' attention to the final price, in particular, when the number of surcharges is high. In addition, the sequential disclosure of the final price lowers perceived price fairness because of higher perceived price complexity and lower pricing transparency perceptions. The findings suggest that firms need to be aware of both attentional and cognitive effects of the final price disclosure when designing DP.